A smart design of new EU emissions trading could save 61 per cent of mitigation costs - Abrell, Jan; Rausch, Sebastian (ZEW policy brief, 2021)
Carbon pricing is a key instrument for achieving Europe's ambitious climate targets. It is therefore not surprising that reform of the EU carbon market is at the heart of the measures proposed by the European Commission (EC). One important policy innovation would be the introduction of a second emissions trading system in Europe that integrates other sectors like buildings and road transport. This addresses some of the inefficiencies of the existing, fragmented EU carbon markets, but at the same time requires a policy decision with potentially large implications in terms of economic costs to achieve European climate goals: How should the EU carbon budget be divided between two separate carbon markets? Achieving the EU climate target of 55 per cent causes a decrease in the aggregate consumption level of the EU-27 countries of 2.8 per cent or 248.9 billion euros in 2030 under current EU climate policy (without considering possible benefits from avoided climate change damages). A new emissions trading system reduces these costs by 21.5 per cent under the current allocation of the EU climate budget and by 33.0 per cent under the allocation proposed by the European Commission. Larger cost reductions of up to 61.6 per cent are possible if an even larger emissions budget is allocated to the buildings and transport sectors. Given the difficulties to politically determine the allocation of the EU climate budget, market-based flexibility mechanisms are desirable in order to achieve climate targets at the lowest economic cost.
Keywords: Graue Literatur